Profil Literasi Lingkungan Siswa SMA N 1 Gemuh - Hikmah, Nur; Nugroho, Ary Susatyo; Patonah, Siti (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Environmental education (EE) plays an important role in instilling environmental awareness character and behavior in students from an early age. This study aims to determine the environmental literacy profile of students at SMA N 1 Gemuh Kendal. This research is a descriptive qualitative research. The research was conducted on 202 grade X students, including ecological knowledge, cognitive skills, awareness of the environment, and environmentally responsible behavior. The data collection was conducted using the Middle School Environmental Litercy Survey (MSELS). The research data were collected through Google Forms and analyzed descriptively based on the achievement score criteria. The results showed that the environmental literacy score was 48.76 in the moderate category. Indicators of ecological knowledge 45.60 (fair), cognitive skills 22.77 (poor), environmental awareness 62.23 (good), and environmentally responsible behavior 64.45 (good). Efforts need to be made so that environmental literacy at SMA N 1 Gemuh reaches an excellent category.